The Utilization of Bacillus Subtilis Bacteria to Improve the Mechanical Properties of Concrete - Sudipto Nath Priyom; Md. Moinul Islam; Wahhida Shumi (Journal of the Civil Engineering Forum, 2021)
The utilization of concrete as a building material is well-known worldwide and increasing continuously due to its sustainability, low maintenance cost, durability, performance, etc. The ingredients of concrete, its constructional methodology, and exposure conditions have been observed to be moderating and improving daily but the focus of this research is on the laboratory investigation of Bacterial Concrete which is the technology established on the application of the mineral producing microbes like Bacillus subtilis which have the properties of bio-calcification and the ability to precipitate CaCO3 effectively inside concrete structures. This CaCO3 precipitation is able to fill the pores and cracks internally and this subsequently makes the structure to become more compact. Nutrient Broth (NB) media was employed for the growth and spore formation of Bacillus subtilis bacteria in this experimental study and four different bacterial culture densities including 0.107, 0.2, 0.637, and 1.221 were estimated at OD600 and directly added to the concrete matrix using the previously fixed water to culture ratio of 0.5:0.5. Moreover, 100 mm cubical concrete specimens were cast, subjected to compressive and tensile strength tests for different curing ages, and finally compared with Conventional Concrete with OD600=0. A significant increase was observed in the mechanical strengths due to the addition of Bacillus subtilis bacteria in concretes with a culture density of 0.637. Furthermore, cylindrical concrete specimens with 100 mm diameter and 200 mm height were prepared for Ultrasonic Pulse Velocity (UPV) analysis and the results showed specimens prepared with culture density of 0.637 have higher pulse velocity than other microbial groups. A UPV vs. compressive strength relationship curve was, however, later proposed for different strengths of concrete.